Magnetic properties and structural analysis on spinel MnFe2O4 nanoparticles prepared via non‐aqueous microwave synthesis. Issue 22 (14th September 2021) - Simon, Christopher; Blösser, André; Eckardt, Mirco; Kurz, Hannah; Weber, Birgit; Zobel, Mirijam; Marschall, Roland
Abstract: Phase‐pure 6 nm spinel MnFe2 O4 nanoparticles with high specific surface area of 145 m 2 g −1 were successfully prepared via microwave‐assisted non‐aqueous sol‐gel synthesis. The phase evolution during postsynthetic thermal treatment was investigated systematically by various methods, including powder X‐ray diffraction (PXRD), pair distribution function (PDF) analysis, and Raman spectroscopy. Our results show that the material decomposes to non‐spinel binary compounds α ‐Mn2 O3 and α ‐Fe2 O3 at temperatures between 400 and 600 °C. The application potential of MnFe2 O4 nanoparticles with 3d 5 Mn(II) and Fe(III) ions with respect to the magnetic properties was demonstrated by superconducting quantum interference device (SQUID) magnetometry, with the as‐synthesized nanoparticles reaching a high saturation magnetization of 2.62 μ B per formula unit (63.5 Am 2 kg −1 ) at 10 K. We further highlight the visible‐light response of synthesized powders, making the materials promising for light‐related applications, e. g . photocatalytic hydrogen evolution. An important additional feature of MnFe2 O4 nanoparticles is their good dispersibilty in polar or non‐polar media, as a result of postsynthetic colloidal stabilization with betaine hydrochloride, oleic acid combined with oleylamine, or citric acid. Abstract :